Pengaruh pengembangan karier terhadap turnover intention pada karyawan - Rizky Tri Hadnianto Nugraheni; Tulus Winarsunu; Ratih Eka Pertiwi (Cognicia, 2022)
Employees generally think about the future of their career goals. This career goal can be achieved by career development, either done by employees or by companies. If there is no clarity about career development, employees will feel exhausted and anxious, which in turn will choose to quit their job and find another job that can help them achieve their predetermined career goals. The purpose of this study was to find out the effect of career development on the turnover intention of employees. This study used a correlational quantitative research design with sampling techniques using incicental sampling. The subjects were employees with permanent status throughout Indonesia with a working period of between 3-5 years and an age range of 25-32 years (N= 104) with a total of 43 males and 61 females. The research instruments used are the adoption scale of career development and Turnover Intention Scale (TIS). Results showed that career development had an influence but not significantly on turnover intention by 2.8%. The remaining 97.2% can be influenced by other variables that are stronger than the studied variables (  = .028; (1) = 2.982; p > .05).   Keywords: career Development, employees, turnover intention